KAJIAN DAMPAK BILINGUAL TERHADAP PERKEMBANGAN KOGNITIF ANAK SEKOLAH DASAR - Ninawati, Mimin (MAJALAH ILMIAH WIDYA, 2012)
In the globalization era, the mastery of foreign language especially English as an international language is compulsory. Nowadaysin Indonesia, English is taught at primary Scholl or even in the kindergarten. The objective of this paper is to discuss the childrenâslearning, particularly from the side of cognitive psychology in learning English as a second language. The phenomena are theadvantages and disadvantages of children who do not learn and learn English as a second language or called monolinguals vs.Bilingualism. The method used library study and the data collected was analyzed descriptively. It is important to note that (1) theelementary school childrens cognitive development is suitable for language learning, (2) There is the advantages to study foreignlanguage at the primary school.(3) The bilingual person is more advantageous than the monolingual person. It is expected that thispaper could be as an insight to see that there are phenomena behind the facts, as a reference to be used as an alternative.